The Relationship Between Husband's Support And The Success Of Normal Delivery In Primigravid Mothers - Cakrawati R; Rezqiqah Aulia Rahmat; Fara Khanza Azizah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Husband's support is a crucial factor influencing a mother's psychological well-being during pregnancy and childbirth. In primigravida mothers, husband's support has been shown to increase self-confidence, reduce anxiety, and contribute to a successful vaginal delivery. This study aimed to analyze the relationship between husband's support and the success of vaginal deliveries in primigravida mothers at Community Health Center X. The study used a cross-sectional design, involving 82 primigravida mothers who gave birth in the last six months. Data were collected using a husband support questionnaire and medical records of the delivery process. Analysis used the Chi- Square test. The study results showed that primigravida mothers who received high levels of husband support were more likely to experience normal delivery than those with low levels of support (p=0.001). Husband support plays a role in reducing anxiety, increasing mental readiness, and strengthening the mother's adaptation to the labor process.